Evaluation of genetic variation in the double-strand break repair pathway and bladder cancer risk - Figueroa, Jonine D.; Malats, Núria; Rothman, Nathaniel; Real, Francisco X.; Silverman, Debra; Kogevinas, Manolis; Chanock, Stephen; Yeager, Meredith; Welch, Robert; Dosemeci, Mustafa; Tardón, Adonina; Serra, Consol; et al. (Carcinogenesis (New York), 2007)
The double-strand break DNA repair (DSBR) pathway is implicated in maintaining genomic stability and therefore could affect bladder cancer risk. Here we present data evaluating 39 single-nucleotide polymorphisms (SNPs) in seven candidate genes whose products are involved in DNA break sensing (NBS1, BRCA1 interacting genes BRIP1 and ZNF350), non-homologous end-joining (NHEJ) DNA repair (XRCC4) and homologous recombination (HR) repair (RAD51, XRCC2 and XRCC3). SNPs for RAD51 and XRCC2 covered most of the common variation. Associations with bladder cancer risk were evaluated in 1150 newly diagnosed cases of urinary bladder transitional cell carcinomas and 1149 controls conducted in Spain during 1997–2001. We found that the genetic variants evaluated significantly contributed to bladder cancer risk (global likelihood ratio test P = 0.01). Subjects with the ZNF350 R501S (rs2278415) variant allele showed significantly reduced risk compared with common homozygote variants, odds ratio (OR) [95% confidence interval (95% CI)]: 0.76 (0.62–0.93) per variant allele. Carriers of a putative functional SNP in intron 7 of XRCC4 (rs1805377) had significantly increased bladder cancer risk compared with common homozygotes: 1.33 (1.08–1.64) per variant allele. Lastly, XRCC2 homozygote variants for three promoter SNPs (rs10234749, rs6464268, rs3218373) and one non-synonymous SNP (rs3218536, R188H) were associated with reduced bladder cancer risk (ORs ranging from 0.36 to 0.50 compared with common homozygotes). Meta-analysis for XRCC3 T241M (rs861539) had a significant small increase in risk among homozygote variants: OR (95% CI) = 1.17 (1.00–1.36). Results from this study provide evidence for associations between variants in genes in the DSBR pathway and bladder cancers risk that warrant replication in other study populations.